Stabilization of thermal breakdown development in semiconductor films - Andreyeva, N.V.; Virchenko, Yu.P. (Вопросы атомной науки и техники, 2004)
The analysis of fixed points of the evolution equation for temperature in thermal fluctuation area in semiconductor film is done. It is shown that there exists a stable fixed point being more than the threshold of the breakdown regime development. Проведено аналiз нерухомих точок еволюцiйного рiвняння для температури в областi теплової флуктуацiї у напiвпровiдниковiй плiвцi. Доведено, що існує нерухома стійка точка, яка є більшою за величиною порогу виникнення режиму пробою. Проведен анализ неподвижных точек эволюционного уравнения для температуры в области тепловой флуктуации на полупроводниковой плёнке. Показано, что существует устойчивая неподвижная точка, большая по величине порога возникновения режима пробоя.